Age and the anaesthetist: considerations for the individual anaesthetist and workforce planning: Guidelines for the ageing anaesthetic workforce from the Association of Anaesthetists. (29th September 2022) - Davies, M.; Clyburn, P.; Barker, P.; Flatt, N.; Noble, N.; Swart, M.; Redfern, N.; Davidson, R.; Fleming, R.; Stacey, K.; Richards, C.
Summary: There is clear evidence of a growing workforce gap and this is compounded by demographic data that show the current workforce is ageing. Within the current workforce, more doctors are taking voluntary early retirement and the loss of these experienced clinicians from departments can have wide‐ranging effects. Older doctors are at risk of age‐related health problems (e.g. sight, musculoskeletal, menopause) and are more susceptible to the effects of fatigue, which may increase the risk of error and or complaint. The purpose of this working party and advocacy campaign was to address concerns over the number of consultants retiring at the earliest opportunity and whether a different approach could extend the working career of consultant anaesthetists and SAS doctors. This could be viewed as 'pacing your career'. The earlier this is considered in a clinician's career the greater the potential mitigation on individuals.